Shura and its rulings in the Islamic ruling system (Journal of the College of Basic Education, 2022)
Islam did not leave any issue of life in its various aspects without addressing it either in its principles orand its totalities or in its parts and details, and based on that, Islam regulated the political aspect of society. He laid the foundations and principles that guarantee the rights of individuals in the Islamic society.Among the principles of the system of government in Islam, which was emphasized by the principle of (consultation).Sharia and the determination of rulings and the glories of Islam, which educates its followers on discussion and dialogue, and the exchange of Opinions on private and public issues.